Hirursko lijecenje metastaza kolorektalnog karcinoma - Škrbić, Velimir; Simatović, Milan; Janjić, Goran; Šaran, Dalibor (Scripta Medica, 2020)
Background/Aim: Colorectal metastatic liver tumours are the most common secondary liver tumours. During the life of patients with colorectal tumorous, this liver metastases will develop either synchronously or metachronously in half of the patients. Approximately 25 % of patients with colorectal cancer diagnosis have secondary deposits in the liver and the additional 25 % of patients will develop metastases within five years. The objective was to investigate whether anatomic resections of the liver present a method of choice in surgical treatment of colorectal liver metastases compared to metastasectomy surgery. Methods: A total of 65 patients were divided into two groups. Patients in the first group underwent metastasectomies consisting in the removal of metastases and the surrounding liver parenchyma no more than 1 cm by Kelly clamp crushing technique or LigaSure vessel-sealing system. Patients in the second group were subjected to the anatomic resection of the liver where not only metastases were removed, but also the associated anatomical segment or section or half the liver, depending on the number and localisation of metastases. Results: The mean values (± standard deviation) of the overall survival for the first and the second group were 36 ± 4.8 months and 36 ± 2.6 months, respectively. The mean values (± standard deviation) of the disease-free survival in the first and in the second group were 18 ± 2.22 months and 22 ± 0.74 months, respectively. None of the found inter-group differences were statistically significant. Conclusion: It can be concluded that metastatic surgery for colorectal liver metastases and anatomic resections have almost the same results and are irreplaceable methods in the treatment of colorectal liver metastases.